Surgical Principles in Inguinal Hernia Repair A Comprehensive Guide to Anatomy and Operative Techniques (Springer International Publishing, 2018)
This text is designed to present a comprehensive state-of-the-art approach to options available for inguinal hernia repair. Early chapters address anatomic evaluation of the groin, preoperative optimization of outcomes, and considerations in choosing a surgical technique. It then transitions to the clinical management of this common medical condition, specifically focusing on operative details. Written by experts in the field of hernia repair, the clinical chapters detail both open and minimally invasive techniques for repair including detailed anatomic drawings, surgical photos, and links to videos of operative techniques. Postoperative management is explained, detailing the common complications and addressing the importance of surgical outcomes, especially in the setting of "pay for performance" metrics. The final section of the text concludes with the management of inguinal hernias in select situations, including children, those performed with concomitant procedures, and modifications for training residents in this common surgical procedure. Each chapter includes a review of the published literature and selected references, along with anatomic illustrations, videos from operative interventions, and surgical photos to help reinforce the text. Surgical Principles in Inguinal Hernia Repair: A Comprehensive Guide to Anatomy and Operative Techniques serves as a comprehensive resource for surgeons on patient preparation, surgical techniques, and outcomes for the management of inguinal hernias. .